Analisis Kepuasan Pelanggan Berbelanja Produk Nutrifood pada PT. Sumber Fajar Inti Abadi - Edy Suryadi; Julistiana 01 (Universitas Muhammadiyah Pontianak, 2014)
The purpose of this study was to analyze customer satisfaction Nutrifood product shopping at PT.Sumber Fajar Inti Abadi. The variables analyzed were the presence, responsiveness, fun, and timely. The research method used survey methods, data collection techniques, namely: observation, questionnaires, and interviews. The samples used were as many as 100 people were using purposive sampling technique, quantitative data analysis techniques through Cartesian diagram. The results of this study indicate that the respondents are not satisfied with the service PT. Sumber Fajar Inti Abadi with an average satisfaction level of 3.43 and an average rating of 3.45 interest rate, dimensions of service quality customer service is the most satisfying and enjoyable responsiveness dimension where all respondents rating is in quadrant B, which means that the interest and customer satisfaction is at a high level and in accordance with the wishes of the customer. While the dimensions of existence and exact time at which the respondent's assessment is in quadrant C, which means that the interest and customer satisfaction is at a low level and not in accordance with the wishes of the customer.